(untitled) (Revista Paradigma, 2019)
This article analyzes the financial citizenship from the point of view of credit and its implications for the lives of people and society, since it has undergone major structural changes, transforming itself into a consumer society. The volatility of trade and events has led to unthinking consumption and with this the population’s debt has reached alarming levels. Interest as a product became attractive to the financial market and the population bowed to this facility. The financial citizenship established by the Central Bank has its place, since it provides financial education to those who already have some income and does not know the economy to invest in the best way. In turn, a credit system is necessary for those who have nothing, so that they can invest, have their own gain and thus have a decent living condition, providing them with conditions of empowerment. It is the credit policy of Grameen Bank, which offers unsecured credit, and has helped change the lives of millions of people. The research used the analytic-deductive method, and was referenced by the thought of Zigmunt Bauman, Boaventura de Sousa Santos and Muhammad Yunus, and was based on books, scientific articles and publications available on the internet.